Effects of Tillage and Crop Rotation on Chemical Phosphorus Forms and Some Related Biological Activities in a Chilean Ultisol - Escudey-Castro, A; Escudey-Castro, A (2011)
The effect of tillage systems and crop rotation on microbial biomass phosphorus (MBP) and acid phosphatase (P-ase) activity, and the amount of different phosphorus (P) forms measured by 31P-NMR spectroscopy were studied on a field experiment carried out in a temperate Ultisol from southern Chile. Two tillage systems, no tillage (NT) and conventional tillage (CT) and two crop rotations, oat-wheat (OW) and lupine-wheat (LW) were evaluated 4yr after the start of the experiment to determine the effects of such management on some soil biological parameters and P forms at three depths (0-5, 0-10 and 10-20cm). Microbial biomass P ranged from 6.5 to 22.6mg/kg, whereas the mean total P (PT) was 1995mg/kg for all treatments (OW and LW). Microbial biomass carbon (MBC) and surface P accumulation (at 0-5cm depth), including Olsen P, MBP, orthophosphate monoesters (monoester-P), were larger under NT than CT. Tillage effects were greater than crop rotation effects in enhancing P availability. The LW rotation showed enhanced P-ase activity and increased monoester-P forms (57 vs. 30% of the total integral area of the spectra, in average) compared with OW. Nevertheless, OW rotation increased orthophosphate (ortho-P), especially at 10-20cm. Microbial biomass carbon ranged from 532 to 2351mg/kg, which represented 1.2-4.5% of total organic C (Co). Furthermore, MBP correlated positively with MBC (r=0.80), Olsen P (r=0.77), Co (r=0.77), pH (r=0.65), PT (r=0.65) and P-ase activity (r=0.57), suggesting the importance of the microbial biomass on soil P availability. © 2011 The Authors. Journal compilation © 2011 British Society of Soil Science.